Time-resolved Hubble Space Telescope UV Observations of an X-Ray Quasiperiodic Eruption Source - T. Wevers; M. Guolo; S. Lockwood; A. Mummery; D. R. Pasham; R. Arcodia (The Astrophysical Journal Letters)
X-ray quasiperiodic eruptions (QPEs) are a novel mode of variability in nearby galactic nuclei whose origin remains unknown. Their multiwavelength properties are poorly constrained, as studies have focused almost entirely on the X-ray band. Here, we report on time-resolved, coordinated Hubble Space Telescope far-ultraviolet (FUV) and XMM-Newton X-ray observations of the shortest period X-ray QPE source currently known, eRO-QPE2. We detect a bright UV point source ( L _FUV ≈ few × 10 ^41 erg s ^−1 ) that does not show statistically significant variability between the X-ray eruption and quiescent phases. This emission is unlikely to be powered by a young stellar population in a nuclear stellar cluster. The X-ray-to-UV spectral energy distribution can be described by a compact accretion disk ( ${R}_{{\rm{out}}}=34{3}_{-138}^{+202}\,R_{{\rm{g}}}$ ). Such compact disks are incompatible with typical disks in active galactic nuclei, but form naturally following the tidal disruption of a star. Our results rule out models (for eRO-QPE2) invoking (i) a classic active galactic nucleus accretion disk and (ii) no accretion disk at all. For orbiter models, the expected radius derived from the timing properties would naturally lead to disk-orbiter interactions for both quasi-spherical and eccentric trajectories. We infer a black hole mass of log _10 ( M _BH ) = 5.9 ± 0.3 M _⊙ and an Eddington ratio of 0.13 ${}_{-0.07}^{+0.18}$ ; in combination with the compact outer radius, this is inconsistent with existing disk instability models. After accounting for the quiescent disk emission, we constrain the ratio of X-ray to FUV luminosity of the eruption component to be L _X / L _FUV > 16−85 (depending on the intrinsic extinction).